Transcanal endoscopic surgery of soft tissue giant cell tumor of the ear canal - Vinota Paniselvam; Muhammad Hazmi Akashah; Siti Hajar Sanudin; Mohd Fariz Amri; Irfan Mohamad (BioMed Central Ltd, 2025)
Background Primary giant cell tumor of the soft tissue (GCT-ST) of the external auditory canal (EAC) is a rare entity with very limited data available regarding the treatment approach. We aim to describe the surgical technique used for tumor excision and the benefits of this approach. Case presentation A 25-year-old man who presented with an isolated EAC mass and underwent excision of the mass via the trans canal endoscopic ear surgery (TEES) approach. Histopathological examination of the tumor revealed a GCT-ST of the EAC. Conclusion Surgical management of GCT-STs of the ear canal is technically challenging due to the narrow region. The TEES approach has shown advantages for the excision of EAC tumors. It provides a wider view during tumor excision which leads to a good outcome after excision.